Phytodiversity Inventorisation and Mapping of Shola Grasslands of Kodaikanal Wildlife Sanctuary, Western Ghats, India - Arigela, Ravi Kiran; Singh, R. KR.; Kabeer, K. A. A.; Murthy, G. V. S.; Robin, V. V. (Indian Forester, 2019)
During the course of floristic studies of Kodaikanal Wildlife Sanctuary, mapping of Shola grasslands and savannah of Kodaikanal wildlife sanctuary was done. In this study 7 grasslands were reported and categorized into 4 types based on species dominance. Apart from this, a total 155 angiospermic species of 33 families were reported, in which 42 are grass species and 113 are grassland associated species. Out of 155 total species, 13 are endemic grasses and 43 are endemic grassland associated species. Factors affecting the ecosystem of grasslands are given and conservation measures are suggested to protect the natural composition of the grasslands.